Fetal acute cerebral vasoreactivity to maternal hyperoxia in low‐risk pregnancies: a cross‐sectional study. (20th April 2020) - Sanapo, Laura; Al‐Shargabi, Tareq; Ahmadzia, Homa K.; Schidlow, David N.; Donofrio, Mary T.; Hitchings, Laura; Khoury, Alfred; Larry Maxwell, G.; Baker, Robin; Bulas, Dorothy I.; Gomez, Luis M.; du Plessis, Adre J.
Abstract: Objective: To establish whether fetal cerebral vasoreactivity (CVRO2 ), following maternal hyperoxia, is predicted by fetal cerebral and uteroplacental Doppler pulsatility indices (PI) at baseline, fetal pulmonary vasoreactivity to oxygen (PVRO2 ), gestational age (GA), or sex. Methods: Pulsatility index of middle (MCA), anterior (ACA), posterior cerebral (PCA), umbilical (UA), uterine (UtA), and branch of the pulmonary arteries (PA) were obtained, by ultrasound, before (baseline), during (hyperoxia) and after 15 minutes of maternal administration of 8 L/min of 100% oxygen, through a non‐rebreathing face mask, in normal singleton pregnancies within 20 to 38 weeks' gestation. CVRO2 was defined as changes greater than zero in z score of PI of the cerebral arteries from baseline to hyperoxia. Logistic modeling was applied to identify CVRO2 predictors. Results: A total of 97 pregnancies were eligible. In the overall population, median z scores of PI of MCA, ACA, and PCA did not differ between study phases. Based on the logistic model, baseline z scores for cerebral PI and GA were the best predictors of CVRO2 . Conclusions: In low‐risk pregnancies, fetal CVRO2 to hyperoxia does not occur uniformly but depends on cerebral PI and GA at baseline. These findings may provide useful reference points when oxygen is administered in high‐risk pregnancies.